2020
DOI: 10.1002/cb.1798
|View full text |Cite|
|
Sign up to set email alerts
|

How do I see myself? A systematic review of identities in pro‐environmental behaviour research

Abstract: Encouraging pro‐environmental behaviour (PEB) is an environmental and societal concern. Encouraging PEB focussing on how consumers see themselves (their identity) has blossomed. However, a theoretical assessment of this research is missing. Three main identity theories seem to best explain the research, specifically, and two‐fold, identity, and social identity theory (SIT), collectively known as the unified identity theory (UIT), and place identity theory (PIT). As these theories overlap more than differ in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(76 citation statements)
references
References 117 publications
1
57
0
2
Order By: Relevance
“…How they see themselves is an essential factor affecting consumer behaviour (Udall, de Groot, de Jong, & Shankar, 2020), when the self‐discrepancy increases, consumers would lead to compensatory consumption behaviour (Mandel et al., 2017). Compensatory consumer behaviour indicates any purchase, use or consumption of products or services motivated by a desire to offset or reduce a self‐discrepancy (Rucker & Galinsky, 2008).…”
Section: Theory Development and Research Hypothesismentioning
confidence: 99%
“…How they see themselves is an essential factor affecting consumer behaviour (Udall, de Groot, de Jong, & Shankar, 2020), when the self‐discrepancy increases, consumers would lead to compensatory consumption behaviour (Mandel et al., 2017). Compensatory consumer behaviour indicates any purchase, use or consumption of products or services motivated by a desire to offset or reduce a self‐discrepancy (Rucker & Galinsky, 2008).…”
Section: Theory Development and Research Hypothesismentioning
confidence: 99%
“…However, it has been argued that the distinction between social and personal identity may often not be necessary as the process of dealing with identity-congruent feedback is the same whether the identity has its origin in the social or the personal sphere (Reed et al, 2012). Similarly, Udall et al (2020) argue that the identity approach suggested by Stets and Burke (2000) and social identity theory (Tajfel, 1981) should be understood in an integrated way. According to both theories, individuals have the capacity to reflect upon and categorize themselves with respect to personally based features (e.g., personality, appearance, and behavior), roles they occupy, groups they belong to (in-groups) and groups to which they do not belong (out-groups; Stryker & Burke, 2000;Tajfel, 1981).…”
Section: Multiple Identities and Conflict Resolution Strategiesmentioning
confidence: 99%
“…However, identity research struggles with a fragmented terminology and lack of an integrated framework (M. A. Hogg et al, 1995;Reed et al, 2012;Udall et al, 2020). It is clear from extant research that people may have multiple identities due, among other things, to an ever-increasing number of roles and group memberships.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Udall et al (2020), the email address of the corresponding author appeared incorrectly in the published version. The correct email address should be alinamiaudall@bath.edu.…”
mentioning
confidence: 99%